The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s13193-021-01424-3
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Surgery During COVID-19 Pandemic: Experience from a Tertiary Care in India

Abstract: Head and neck pathologies requiring surgical intervention are considered a high-risk subsite in the context of COVID-19 pandemic by virtue of its close proximity to the mucosa of the upper aerodigestive tract. Retrospective review of all head and neck surgical procedures is undertaken during the pandemic from 23rd April 2020 to 30th September 2020. One hundred procedures were performed on 98 patients. COVID-19 status determined by SARS-Cov-2 RT-PCR at baseline was negative for 81, positive in 8 and unknown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Above all, these trials reported no claims for any COVID-19 screenings or prevention strategies. Panda et al [ 41 ] discovered that the application of the protection strategies led to a reduction in the post-operative problems both at times before and after the pandemic, as well as a decreased rate in the complications in a matched pair analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Above all, these trials reported no claims for any COVID-19 screenings or prevention strategies. Panda et al [ 41 ] discovered that the application of the protection strategies led to a reduction in the post-operative problems both at times before and after the pandemic, as well as a decreased rate in the complications in a matched pair analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Above all, these studies did not claim any specific screening or preventing protocols for COVID -19. In contrast, with the use of protection protocols, Panda et al found a significant decrease in major post-operative complications during pandemic, and in a matched pair analysis, lower rate of complications (30). Evidence suggests that surgery care can be continued with adopting preventive strategies and protocols, even in the COVID -19 peak (23,(26)(27)(28)(29)42,49,54).…”
Section: Discussionmentioning
confidence: 99%
“…Using experienced physician to avoid exposure of junior doctors and shorten the duration of procedures (23,30,41,42,47,49,53) Self-isolation Asking patient to be selfisolate (14 days) prior to planned time of surgery (25,32,53,33,35,37,38,41,43,47,48) PCR: Polymerase chain reaction, CT: Computed tomography scan, CXR: Chest X-ray.…”
Section: Experienced Physician/operatormentioning
confidence: 99%